Treating Traumatized Offenders and Veterans by Means of Narrative Exposure Therapy - Hecker, Tobias; Hermenau, Katharin; Crombach, Anselm; Elbert, Thomas (Frontiers in Psychiatry, 2015)
Violent offenders and soldiers are at high risk of developing appetitive aggression and trauma-related disorders, which reduce successful integration into societies. Narrative Exposure Therapy for Forensic Offender Rehabilitation (FORNET) aims at reducing symptoms of traumatic stress (e.g. posttraumatic stress disorder) and controlling readiness for aggressive behavior. It follows the logic of the evidence-based trauma-focused Narrative Exposure Therapy (NET) with special emphasis on violent acts in past and future behavior. In NET the therapist guides the client by means of exposure through his traumatic experiences in chronological order linking the negative emotions, such as fear, shame and disgust, to the past context and integrating the traumatic experiences into the autobiographical memory. During FORNET we also encourage verbalization of any positive emotions and experiences linked to past violent and aggressive behaviors. This recall of positive emotions (linked to the there and then) is contrasted with feelings that emerge during the narration process (here and now). In this way, the therapist helps the client to anchor the whole range of sensory and bodily experiences, cognitions, and emotions to the contextual cues. Over the process of the therapy we support the client to begin the role change from a violent offender to a citizen, who is capable of living a non-violent and socially adjusted life. Finally, the client develops visions and wishes for the future to support a successful integration into society. Several studies with veterans and violent youths have proven the feasibility of FORNET, found evidence of a positive outcome (recovered mental health, fewer offenses committed, less drug intake and improved integration into civil society), and highlighted the importance of addressing the whole range of experiences while treating violent offenders or veterans.